Persuasing Text E-Modin Development Contents Love the Environment for Class VIII Students SMPI Al Fattaiyyah Tulungagung - Qoyyimun Nafal; Dyah Werdiningsih; Sri Wahyuni (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
This study aims to determine the development of E-modin persuasive texts with love for the environment for class VIII students of SMPI Al Fattaiyyah Tulungagung. This research uses a development research model or is called the R&D (Research and Devolepment) model. The result of the research is that the product evaluation of the development of e-modin persuasive texts with love for the environment for class VIII students of this junior high school is based on the stated objectives, which include the results of product development and feasibility. The results of the development are in the form of the resulting product, while the feasibility of the product is in the form of an assessment of the product seen from the learning design aspects, material/content aspects, linguistic aspects, and media aspects. Eligibility is used to indicate the ease and suitability of using e-modin. Data regarding the analysis of development research needs were found by researchers during field surveys and literature studies. The information obtained by the researcher was 1) the persuasion text teaching materials used were in the form of textbooks from the Ministry of Education and Culture, 2) persuasion texts were the most difficult texts to teach and mastered by students, 3) teaching materials from the Ministry of Education and Culture contained material that was general and less specific and less interactive so that it requires accompanying teaching materials so that the material delivered is more varied, and 4) practice questions for persuasive texts need to be added or enriched, not just making example sentences, answering questions, and identifying texts.